Dorsal Dislocation of the Intermediate Cuneiform with a Medial Cuneiform Fracture: A Case Report and Review of the Literature - Burak Akan; Tugrul Yildirim (Case Reports in Orthopedics)
Dorsal dislocation of the intermediate cuneiform and isolated medial cuneiform fractures are rare injuries. In this report, we present a patient who sustained a dislocation of the intermediate cuneiform and describe predisposing factors and the treatment procedure.